(3GdeNJGQ GdLGeY dHjf GdefJbi hGdGSJPcGQs - (3CHh YHO Gddg eMeO Hf YHO GdMb Hf SdjeGf GdjYaQi GdJdeSGfis
(3ChdgG (B:s
(3CMeO ddg ChdkG Ke jYed eG CeJf Hg ef Pdc Ydi Ndbg CfRd GdcJH hCQSd GdQSd s
(3BNQgG (B:s
(3jfJgi HHGH G(B" (3LGeY ZSd GdLfGHI (B" (3hBNQ eG ajNg hdh cGf GdeGA cKjQkG jMed eG jbY ajg dLGR Pdc hEf de jZSd Yfg GdCPi s
(3CcKQ GdfSNI Ydi Qb ZRGds
(3HChdgG NW GdeDQN eMeO Hf GdWjH GdbGOQi GdMSf UGMH cJGH fTQ GdeKGfis
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3HgG NQe s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdMOjK h GdeUWdMs